Effect of heterotrigona itama bee bread on metabolic dysfunction-associated fatty liver disease parameters in obese male rats - Zakaria, Zaida (2022)
Almost 13 % of the world population suffers from obesity. Metabolic dysfunction‐associated fatty liver disease (MAFLD) is a pathological accumulation of hepatic lipid resulted from obesity and closely linked with many metabolic disorders, oxidative stress, inflammation and apoptosis. Bee bread has been reported to contain phenolic compounds and exhibits antioxidant, anti-inflammatory, and antiapoptotic properties. In addition, it significantly reduced the hepatic levels of lipogenic genes in MAFLD rat model. However, to date, it is not known whether bee bread may also improve other parameters in MAFLD. Therefore, the present study aimed to determine the phenolic composition of Heterotrigona itama bee bread and the effect of this bee bread on MAFLD parameters in obese male rats. Forty adult male Sprague Dawley rats weighing between 200-230 g were randomly divided into four groups (n=10/group): normal control (NC), high‐fat diet (HFD), bee bread (HFD+Bb, HFD+0.5 g/kg/day bee bread) and orlistat (HFD+Or, HFD+10 mg/kg/day orlistat) groups. At the end of 12th week, rats were sacrificed to obtain serum, adipose and liver tissues. Nine phenolic compounds were discovered with trans 3- hydroxycinnamic acid as the highest amount of compound to be found in the bee bread. Bee bread significantly improved liver function and histopathological changes in MAFLD rats. It also significantly down-regulated genes related to fatty acid uptake and de novo lipogenesis, up-regulated genes related to lipolysis, fatty acid β- oxidation and bile acid synthesis in the liver, hence improved hepatic lipid metabolism. Furthermore, bee bread significantly reduced liver oxidative stress markers (thiobarbituric acid reactive substance, nitric oxide, protein carbonyl), elevated antioxidant enzyme activities (superoxide dismutase, catalase, glutathione peroxidase, glutathione S-transferase, glutathione reductase) and translocation of nuclear factor erythroid 2‐related factor 2 to the nucleus, as well as mitigated proinflammatory (tumour necrosis factor-α, nuclear factor-kappa β, interleukin-1β, monocyte chemoattractant protein‐1) and pro-apoptosis (Bax, caspase-3) markers, which may be attributed to the presence of phenolic compounds in the bee bread. However, further studies are needed to elucidate other molecular mechanisms of bee bread before it is used as an alternative or complementary therapy among obese patients with MAFLD.